Applying CBM and PHM concepts with reliability approach for Blowout Preventer (BOP): a literature review - Brandão Martins, Filipe; Cardoso, Rodolfo; Tammela, Iara; Colombo, Danilo; Acioli de Matos, Bruno (Brazilian Journal of Operations & Production Management, 2018)
The sensibility originated by the Blowout Preventer (BOP) theme, due to all attention gathered after the Macondo event, established a high level of requirements from regulatory agencies, clients and Drilling Contractors themselves. Based on these pillars, the concept of reliability has been constantly applied in the oil industry, especially in the Well Safety and Control System, where it is extremely important for the equipment to be reliable and operational when required. In parallel, the Condition Based Maintenance (CBM) and Prognostic Health Management (PHM) concepts, widely used in critical industries, which require high reliability levels, are being pointed out as the future for the BOP system management. Within this context, the purpose of this paper is to review the literature on Condition Based Maintenance and Prognostic Health Management, integrated with reliability concepts, and to enable them to be applied in the BOP health management. The paper identifies different concepts needed to support the main theme and, through research and selection criteria, it brings together a set of publications to obtain consistent theoretical framework. This research outlines important techniques used in high reliability industries and the way they can be applied on the BOP system and it also provides many useful references and case studies to assist on further development works in terms of well control and operational safety.